The relationship between stress, social support, and quality of life among spouses of patients at the end-of-life stage in Thailand: A correlational study - Rathapon Thawonphat; Tiraporn Junda; Bualuang Sumdaengrit (Belitung Nursing Journal)
Background: Non-communicable diseases have become a leading global health challenge, with mortality rates steadily rising. Insufficient patient care can worsen chronic illness, often placing significant caregiving responsibilities on the patient’s spouse. In some cases, spouses may need to leave their jobs to provide full-time care, especially during the end-of-life stage. Spousal caregivers often face emotionally distressing circumstances while caring for their loved ones, which can lead to elevated stress levels. However, research indicates that adequate social support can improve caregivers’ quality of life, reducing some of the burdens associated with end-of-life care.